Study of determinants and predictive risk of cardiovascular disease among adult males in Aligarh: a cross-sectional study - Verma, Sudhir; Shah, Mohammad Salman; Ahmad, Anees; Khalil, Salman (International Journal Of Community Medicine And Public Health, 2026)
Background: Non-communicable diseases (NCDs) result from genetic, physiological, environmental and behavioural factors in combination. NCDs kill around 41 million people a year, equivalent to three-quarters of deaths worldwide. QRISK is a well-established cardiovascular disease (CVD) risk score, in use across the NHS since 2009, which is designed to identify people at high risk of developing CVD who need to be recalled and assessed in more detail to reduce their risk of developing CVD. Methods: This was a cross-sectional study conducted under the department of community medicine in rural and urban health training centre of JNMC AMU, Aligarh, India, during 2019 to 2020 with a sample size of 204. Results: A total of 204 males in the age group of 25 to 84 years were study participants. Among all, 32.8% participants were physically active, 52.0% participants were current smokers, 27.0% participants were overweight, and 5.4% were found to be obese. The prevalence of raised blood sugar was 21.1% and raised blood pressure in 23% participants. According to the QRISK2 score developed in 2017, participants at high risk (≥20%) were 26.5%. Conclusions: Cardiovascular disease risk factors, smoking, lack of physical activity, diabetes, raised blood pressure, overweight and obesity by BMI, and abdominal obesity and also 10-year cardiovascular risk are higher than the studies conducted for these risk factors in India. Health education, early diagnosis should be imparted to the general population.